Solve for y (complex solution)
y=-d+8\sqrt{d}
d\neq 0
Solve for y
y=-d+8\sqrt{d}
d>0
Solve for d (complex solution)
\left\{\begin{matrix}d=-y-8\sqrt{16-y}+32\text{, }&y\neq 0\text{ and }arg(-\sqrt{16-y}+4)<\pi \\d=\left(\sqrt{16-y}+4\right)^{2}\text{, }&arg(\sqrt{16-y}+4)<\pi \end{matrix}\right.
Solve for d
\left\{\begin{matrix}d=-y-8\sqrt{16-y}+32\text{, }&y\neq 0\text{ and }y\leq 16\text{ and }-\sqrt{16-y}+4\geq 0\\d=\left(\sqrt{16-y}+4\right)^{2}\text{, }&y\leq 16\end{matrix}\right.
Graph
Share
Copied to clipboard
\frac{y}{\sqrt{d}}=8-\sqrt{d}
Subtract \sqrt{d} from both sides.
\frac{1}{\sqrt{d}}y=-\sqrt{d}+8
The equation is in standard form.
\frac{\frac{1}{\sqrt{d}}y\sqrt{d}}{1}=\frac{\left(-\sqrt{d}+8\right)\sqrt{d}}{1}
Divide both sides by \left(\sqrt{d}\right)^{-1}.
y=\frac{\left(-\sqrt{d}+8\right)\sqrt{d}}{1}
Dividing by \left(\sqrt{d}\right)^{-1} undoes the multiplication by \left(\sqrt{d}\right)^{-1}.
y=-d+8\sqrt{d}
Divide 8-\sqrt{d} by \left(\sqrt{d}\right)^{-1}.
\frac{y}{\sqrt{d}}=8-\sqrt{d}
Subtract \sqrt{d} from both sides.
\frac{1}{\sqrt{d}}y=-\sqrt{d}+8
The equation is in standard form.
\frac{\frac{1}{\sqrt{d}}y\sqrt{d}}{1}=\frac{\left(-\sqrt{d}+8\right)\sqrt{d}}{1}
Divide both sides by \left(\sqrt{d}\right)^{-1}.
y=\frac{\left(-\sqrt{d}+8\right)\sqrt{d}}{1}
Dividing by \left(\sqrt{d}\right)^{-1} undoes the multiplication by \left(\sqrt{d}\right)^{-1}.
y=-d+8\sqrt{d}
Divide 8-\sqrt{d} by \left(\sqrt{d}\right)^{-1}.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}